If it's not what You are looking for type in the equation solver your own equation and let us solve it.
c in (-oo:+oo)
7-((9*c)/10) = 0
(-9/10)*c+7 = 0
7-9/10*c = 0 // - 7
-9/10*c = -7 // : -9/10
c = -7/(-9/10)
c = 70/9
c = 70/9
| 4m+3.8+m=7 | | h(x)=2x^4-3x^3-27x^2+62x-24 | | 2(1x-1)+1=1 | | 4+2+7= | | (4-2i)+2-7= | | 6+x.=-9 | | X(1.2)=25+x | | c+7=99 | | (-9)-(-1)= | | 3c-4bc+(-7b)+3(2bc-b)=equation | | 37x+1/2-(x+1/4) | | y=-6/7x | | 0.75z=3.15 | | 6x-13=4x-43 | | 1.2x=25 | | 0.6x+0.9=0.9x-0.3 | | 1/3(5)+7 | | -1/14+10/7 | | 4x-3+12-x=148 | | 2.5y=425 | | 6(x-1)+7=4x+2(3+x) | | 8(2x+2y)-4(3xy-(-5x))=equation | | 6+2x/5=10 | | 12r=18 | | x+x-2x+x(9)(8)=56 | | 7/16-1/4 | | 0.35x+0.5(14-x)=.10(43) | | 0.14x=4.2 | | y=-2x^2-98 | | (16x^12y^-18)^3/2 | | 4x-16=-20 | | 15x=50 |